HUBUNGAN TASYRI’ ISLAM DENGAN UNDANG-UNDANG ROMAWI - Sitti Nurkhaerah (Hunafa: Jurnal Studia Islamika, 2007)
Before the advent of Islam in Arab,  Roman  civilization had flourished in many aspects of lives such as in philosophy, art  and science. Even, Roma used to be a centre for Christian civilization so that it had given an influence to  its neighboring lands in abovementioned aspects. However, in respect to the influence of Roman Constitution on Islamic law, a controversy emerges. Some scholars reject the influence but some  support it. How the controversy emerges and  what analysis employed by them to  reject and to support  it. This article elaborates that point.  Kata Kunci: Tasyri’ Islam, Undang-Undang Romawi